PEMETAAN AWAL TERHADAP AIR TERJUN SEBAGAI POTENSI OBJEK WISATA ALAM DI DUSUN BUKITSARI, DESA TEGALLINGGAH - Ida Bagus Arya Yoga Bharata (Wanamukti: Jurnal Penelitian Kehutanan, 2022)
Waterfalls are a tourist attraction that has been widely used for its ecosystem services as Nature-Based Tourism in Bali. However, there are still several waterfall points that have not been recorded in the mapping that has been carried out, one of which is in the Bukitsari Sub-Village, Tegallinggah Village which actually also has an uncharted waterfall. The objectives of this study were 1) to know the general description of the location of the waterfall in Bukitsari Sub-Village, 2) to find out the distribution of waterfalls in Bukitsari Sub-Village, 3) to identify waterfall as a potential tourist attraction in Bukitsari Sub-Village. This research is a descriptive research with spatial analysis. The method used in this research is a field survey which includes observation, documentation and interviews. From the results of the study it can be concluded that in general the location is close to the city of Singaraja. There are two waterfalls in Bukitsari Sub-Village, Tegallinggah Village that not too far from one another because in one river flow. Based on its potential, the waterfall in Bukitsari Sub-Village, Tegallinggah Village has a low potential value, this is because there is no availability of supporters such as extreme sports, there is no accommodation at all except souvenirs by taking pictures at the waterfall, and the location, distance, travel time was is quite long with dirt roads and difficult to reach because of vegetation dense and sharp terrain slope, and there are no institutions and managers.